Use the quadratic formula to solve the equation.

-x^2+5x=3

a.5/2 +- sqrt13/2
b.-5/2 +- sqrt13/2
c.2/5 +- sqrt13/2
d.-2/5 +- sqrt13/2

1 answer

same thing as
x^2 - 5x + 3 = 0

x = (5 ± √13)/2

which is the same as a)
Similar Questions
  1. Use the quadratic formula to solve the equation.-x^2+5x=11 a.5/2 +- sqrt13/2 b.-5/2 +- sqrt13/2 c.2/5 +- sqrt13/2 d.-2/5 +-
    1. answers icon 3 answers
  2. Can you tell me if this is correct.Solve.x^2+6x-4=0 the answer I got is x=-3+sqrt13,-3-sqrt13
    1. answers icon 2 answers
  3. [x-(-6+sqrt13)][x-(-6-sqrt13)](x+6+sqrt13)(x+6-sqrt13) (x+6+sqrt13)(x+6+sqrt13) (x^2+12x+36-sqrt13^2) x^2+12x+36-sqrt13^2
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions